The Relationship between Information and Communication Technology (ICT) Self-efficacy and Technopreneurial Intention - Koe, Wei-Loon; Nordin, Noorain Mohd; Marmaya, Najihah Hanisah (Business Management and Strategy, 2022)
As a developing country, Malaysia needs to develop a greater number of technology-savvy entrepreneurs to encounter the challenges of COVID19 and fourth industrial revolution (IR 4.0). However, the number of young technology-based entrepreneurs in Malaysia is still low. Moreover, not many studies have been done to identify the motivating factors of technology-based entrepreneurship. As such, this study was carried out to identify the influence of information and communication technology (ICT) self-efficacy on technopreneurial intention. A total of 152 students from a Malaysian public university was surveyed through self-administered questionnaire. Multiple regressions analysis was performed to test the hypotheses. The results revealed that three variables, namely Internet general ability, confidence in using computer and competency in using computer significantly influenced technopreneurial intention. Meanwhile, communicative ability did not have any significant relationship with technopreneurial intention. Generally, the findings supported previous studies that ICT self-efficacy played a role in determining an individual’s technopreneurial intention. Specifically, proficiency in computer skills and mastery of Internet general ability should be stressed. As technology-based entrepreneurship continues to play a crucial role in post-COVID19 era, it is important to develop more young and competitive technopreneurs. Thus, this study suggested that government should accentuate science, technology, engineering and mathematics (STEM) education; while education providers should continue to offer ICT courses to the students in order to bolster the development of technopreneurship in the country.